Preparation method of immobilized enzyme, immobilized enzyme and application thereof, and preparation method of glycerol carbonate

By forming a stable silicone shell on the immobilized enzyme carrier, the problem of inactivation and shedding of the enzyme under the structure of the carrier material and severe reaction conditions is solved, and a high-activity and stable immobilized enzyme is achieved.

CN116042597BActive Publication Date: 2025-04-04HEBEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211441155.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2025-04-04
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

Existing immobilized enzymes are prone to inactivation and shedding under the structure of the support material and severe reaction conditions, resulting in low catalytic activity and instability.

Method used

Dendritic fibrous silicon oxide nanoparticles were prepared using the improved WinsorIII microemulsion bicontinuous phase system, and a stable silicone shell was formed by dichlorodimethylsilane modification and 3-aminopropyltriethoxysilane coating. Immobilized enzyme I reacted with ethyl orthosilicate and 3-aminopropyltriethoxysilane to form Si-O-Si bonds to construct a stable immobilized enzyme.

Benefits of technology

While maintaining high enzyme activity, the stability of immobilized enzymes is significantly improved, the conformation of enzyme molecules is protected, the enzyme molecules are prevented from leaking, and the mechanical stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116042597B_ABST
    Figure CN116042597B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing an immobilized enzyme, an immobilized enzyme and its application, and a method for preparing glycerol carbonate. The method for preparing the immobilized enzyme is to adsorb enzyme molecules on the surface of organosilicon-modified dendritic fiber-shaped silica nanoparticles and coat the organosilicon shell layer to obtain the immobilized enzyme. The immobilized enzyme prepared by the method can effectively protect the conformation of the enzyme molecules, prevent the leakage of the enzyme molecules, improve the mechanical stability of the immobilized enzyme, and realize the interfacial activation of the lipase activity, which is of great significance for expanding the industrial application of immobilized lipase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of enzyme engineering, in particular to a method for preparing an immobilized enzyme. The invention also relates to a method for synthesizing glycerol carbonate by catalyzing the immobilized enzyme. Background Art

[0002] Enzyme is a biological catalyst that can be widely used in biocatalytic reactions. Although free enzymes are widely used and the catalytic technology is relatively mature, they are easily affected by conditions such as pH and temperature and are unstable. They are difficult to separate and can only be used once in most cases. They are not ideal catalysts for industrial applications. Enzyme immobilization technology is one of the effective means to improve the efficiency of enzyme use, achieve continuous operation, and reduce production costs. Enzymes are fixed in different carrier materials, such as porous materials (mesoporous silica, mesoporous titanium dioxide, MOF, COF, etc.), carriers containing multi-electron groups (hydrotalcite, polysaccharides, carbon materials, etc.), and the technology of using solid materials and carriers to restrict free enzymes to a certain area for catalytic reactions. Immobilized enzymes can overcome the shortcomings of free enzymes that are unstable and have low catalytic efficiency, and have the advantages of high recovery rate and can be reused many times. However, the structure of the carrier material will cause the enzyme molecules to be directly exposed to the reaction solution and cause inactivation. On the other hand, the drastic reaction conditions will cause the enzyme molecules to fall off from the loading site and lose enzyme activity. Therefore, the preparation of immobilized enzymes with high catalytic activity and good stability is the focus of research. Summary of the invention

[0003] In view of this, the present invention provides a method for preparing an immobilized enzyme, which can maintain high enzyme activity while having good stability.

[0004] A method for preparing an immobilized enzyme, the method comprising the following steps:

[0005] S1. Hexadecyltrimethylammonium halide, n-butanol, urea aqueous solution and cyclohexane are mixed and dispersed uniformly by ultrasonication; ethyl orthosilicate is added dropwise, stirred uniformly, and then the temperature is raised to 70-80°C, kept warm, and then the solid and liquid are separated by centrifugation, and the solid product is washed, dried and calcined to obtain nano silicon oxide;

[0006] S2, mixing the nano-silicon oxide, dichlorodimethylsilane and toluene, and washing after the reaction to obtain dichlorodimethylsilane-modified nano-silicon oxide;

[0007] S3, taking the enzyme solution, the dichlorodimethylsilane-modified nano-silica and the phosphate buffer solution and placing them in a shaker for shaking, then centrifuging the solid and the liquid for separation, washing the solid with a phosphate buffer solution, and freeze-drying to obtain the immobilized enzyme I;

[0008] S4, mixing the immobilized enzyme I, tris(hydroxymethyl)aminomethane hydrochloride buffer solution and tetraethyl orthosilicate, incubating in a shaker, adding 3-aminopropyltriethoxysilane, and centrifuging the solid and liquid after the reaction; washing the solid with tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and allowing to stand for aging to obtain the immobilized enzyme.

[0009] Furthermore, in step S1, the mass ratio of the dichlorodimethylsilane-modified nano-silicon oxide to the enzyme is 3:(1.5-5).

[0010] Furthermore, in step S4, the mass volume ratio of the immobilized enzyme I to the tetraethyl orthosilicate is 1:(2-2.5).

[0011] Furthermore, in step S4, the mass volume ratio of the immobilized enzyme I to the 3-aminopropyltriethoxysilane is 5:(1-1.5).

[0012] Furthermore, the incubation time in step S4 is 0.5-2h, the incubation temperature is 20-30°C, and the rotation speed of the shaking table is 50-200rpm.

[0013] Furthermore, the enzyme solution includes a lipase solution, or one of oxidoreductases, transferases, hydrolases, lyases, isomerases, and synthetases.

[0014] The preparation method of the immobilized enzyme of the present application is based on the improved WinsorIII microemulsion bicontinuous phase system, and dendritic fiber-shaped silica nanoparticles are prepared, and then the silica nanoparticles are modified by dichlorodimethylsilane to obtain the immobilized enzyme I. Ethyl orthosilicate is added to a certain amount of immobilized enzyme I suspension, and 3-amino-propyltriethoxysilane is added after mixing, and the hydrogen bond and ion interaction with the protein surface are stably combined, thereby inducing organosilicon (Organosilicon, OS) to gradually hydrolyze and condense on the surface of the immobilized enzyme I carrier to form Si-O-Si bonds, and finally form a stable organosilicon shell layer to achieve the construction of the immobilized enzyme. The preparation method of the immobilized enzyme of the present application can have good stability while maintaining a high enzyme activity. Further, by adjusting the coating time to adjust the surface shell thickness, to improve its stability, the enzyme molecular conformation can be effectively protected, the enzyme molecule leakage can be prevented, and the mechanical stability of the immobilized enzyme can be improved.

[0015] The present application also proposes an immobilized enzyme, which is prepared by the above-mentioned method for preparing the immobilized enzyme.

[0016] The present application further proposes an application of the above-mentioned immobilized enzyme. When the enzyme solution is a lipase solution, the immobilized enzyme is used to catalyze transesterification reaction, hydrolysis reaction, and esterification reaction.

[0017] When the immobilized enzyme is used to catalyze the transesterification reaction, since the immobilized enzyme can maintain high enzyme activity while having good stability, the transesterification efficiency of the transesterification reaction enzyme can be improved.

[0018] The present application further proposes a method for preparing glycerol carbonate. When the enzyme solution is a lipase solution, the preparation method uses the above-mentioned immobilized enzyme to catalyze the ester exchange reaction between glycerol and dimethyl carbonate to obtain glycerol carbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0020] Figure 1 Schematic diagram of the preparation method of the immobilized enzyme of the present invention;

[0021] Figure 2 This is a SEM image of CALB@DFSP of Example 1 of the present invention;

[0022] Figure 3 TEM image of CALB@DFSP of Example 1 of the present invention;

[0023] Figure 4 N2 adsorption-desorption curves of CALB@DFSP-OS-4h, CALB@DFSP-OS-8h and CALB@DFSP-OS-12h of Example 1 of the present invention;

[0024] Figure 5 IR spectra of CALB@DFSP and CALB@DFSP-OS of Example 1 of the present invention;

[0025] Figure 6 This is a graph showing the relative activity of CALB@DFSP-OS at different coating times according to Example 1 of the present invention;

[0026] Figure 7 This is a diagram showing the mechanical stability of CALB@DFSP-OS according to Example 1 of the present invention;

[0027] Figure 8 This is a graph showing the activity of CALB@DFSP-OS and free enzyme CALB in Example 1 of the present invention changing with time at pH = 4.0;

[0028] Fig. 9 This is a thermal stability diagram of CALB@DFSP-OS and free CALB of Example 1 of the present invention at 60°C;

[0029] Fig.10This is a storage stability diagram of CALB@DFSP-OS of Example 1 of the present invention;

[0030] Fig.11 This is a graph showing the reusability of CALB@DFSP-OS, CALB@DFSP and lipase N435 of Example 1 of the present invention. DETAILED DESCRIPTION

[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0032] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified. In addition, except for special instructions in this example, the terms and processes involved in this example are understood according to the general knowledge and conventional methods in the prior art.

[0033] A method for preparing an immobilized enzyme, the method specifically comprising the following steps:

[0034] S1. Add hexadecyl trimethyl ammonium halide, n-butanol, urea aqueous solution (0.4M) and cyclohexane to a 100mL round-bottom flask and mix, ultrasonically disperse for 30min to make the emulsion uniform, then stir slightly to observe whether it is uniform. The above operation can be carried out at room temperature. Then, add tetraethyl orthosilicate (TEOS) dropwise, stir for 30min, and after tetraethyl orthosilicate is uniformly dispersed, heat up to 70-80°C, keep warm for 20-24h, then centrifuge the solid and liquid, wash the solid product with ethanol, and calcine in a resistance furnace after drying, the calcination temperature is 550-600°C, and the time is 5-5.5h to obtain white powder, i.e., nano silicon oxide (Dendriticfibrous silica nano-particles, DFSP). Wherein hexadecyl trimethyl ammonium halide can preferably be hexadecyl trimethyl ammonium bromide (CTAB).

[0035] S2, mixing nano silicon oxide (DFSP), dichlorodimethylsilane and toluene, washing the solid matter with toluene and ethanol after the reaction is completed at room temperature to obtain nano silicon oxide modified with dichlorodimethylsilane;

[0036] S3, take 5mL of enzyme solution, nano-silica modified by dichlorodimethylsilane and 50mM phosphate buffer solution (PBS), put them into a 10mL centrifuge tube, place them in a shaker at room temperature for 2.5-3h, then centrifuge the solid and liquid, wash the solid with phosphate buffer solution, and obtain immobilized enzyme I after freeze drying. In this step, the enzyme is adsorbed to the pores of DFSP modified by dichlorodimethylsilane. The preferred mass ratio of nano-silica modified by dichlorodimethylsilane (50mg) to the enzyme is 3: (1.5-5), and the actual mass ratio can also be adjusted according to the concentration and dosage of the enzyme. The enzyme solution can be used according to different catalytic requirements, including one of lipase solution, amylase solution, and protease solution. The "adsorption" means that when a substance (which can be a gas, liquid or solid) contacts a porous solid, the substance accumulates on the surface of the solid (especially on the surface where the pores are formed).

[0037] S4, take immobilized enzyme I, tris-HCl buffer solution, and tetraethyl orthosilicate, mix them, and incubate them in a shaker. Then add 3-aminopropyltriethoxysilane (APTES), and centrifuge the solid and liquid after the reaction. The reaction time can be selected according to the designed silicone coating, 2-12h, such as 2h, 4h, 6h, 8h, 10h, 12h. Take the solid and wash it with tris-HCl buffer solution, and let it stand in the above buffer solution at 25°C for aging for 12h to obtain the immobilized enzyme. In this step, the mass volume ratio of immobilized enzyme I to tetraethyl orthosilicate is 1: (2-2.5), and the mass volume ratio of immobilized enzyme I to 3-aminopropyltriethoxysilane is 5: (1-1.5). The ratio of the above raw materials can also be selected according to the thickness of the silicone coating. The incubation time of this step is preferably 0.5-2 h, the incubation temperature is 20-30° C., and the rotation speed of the shaker is 50-200 rpm.

[0038] The preparation method of the immobilized enzyme of the present application is based on the improved WinsorIII microemulsion bicontinuous phase system, and dendritic fiber-shaped silicon oxide nanoparticles are prepared. Hexadecyl trimethyl ammonium halide is a cationic active agent, has surface activity, and the hexadecyl line arrangement is the hydrophobic end, and the quaternary ammonium end is the hydrophilic end, and the quaternary ammonium group presents positive charge when dissolved in water. A plurality of hexadecyl trimethyl ammonium halides and n-butanol are mixed and arranged in the microemulsion bicontinuous phase system, and are used as templates to hydrolyze tetraethyl orthosilicate, forming dendritic fiber-shaped silicon oxide nanoparticles with surface wrinkles, and the dendritic fiber-shaped silicon oxide nanoparticles have huge specific surface area and have strong adsorption performance. But silicon oxide particles belong to hydrophilic materials, and their dispersibility in organic solvents is poor, so the inventor carries out modification of organosilane and silicic acid condensation to silicon oxide, so that its hydrophobic property is improved, and it is easier to disperse in organic phase, and is used as enzyme carrier, and can contact substrate more fully after compounding with enzyme, and improves the catalytic efficiency of enzyme.

[0039] Specifically, dichlorodimethylsilane is reacted with silicon oxide nanoparticles to graft methyl groups on the surface of silicon oxide nanoparticles, and then the enzyme is adsorbed to obtain immobilized enzyme I. Subsequently, ethyl orthosilicate is added to a certain amount of immobilized enzyme I suspension to perform silica condensation, and then 3-amino-propyltriethoxysilane is added to stabilize the binding through hydrogen bonds and ion interactions with the protein surface, thereby inducing the organic silicon to gradually hydrolyze and condense on the surface of the immobilized enzyme I to form Si-O-Si bonds, and finally forming a stable organic silicon shell layer, thereby realizing the construction of the immobilized enzyme, such as Figure 1 Further, by adjusting the coating time and adjusting the thickness of the surface shell layer to improve its stability, the conformation of the enzyme molecules can be effectively protected, the leakage of the enzyme molecules can be prevented, and the mechanical stability of the immobilized enzyme can be improved.

[0040] The present application also proposes an immobilized enzyme, which is prepared by the above-mentioned method for preparing the immobilized enzyme.

[0041] The immobilized enzyme of the present application is an immobilized enzyme with an organic silicon coating constructed based on the immobilized enzyme I, and the thickness of the surface organic silicon coating can be further controlled by adjusting the coating time. The immobilized enzyme of the present application has high pH stability, thermal stability, and storage stability due to the effective binding of the organic coating and the surface activation of the enzyme.

[0042] The specific implementation scheme of the present invention is described in detail below.

[0043] The reagents used in this example were purchased from the following manufacturers and specifications:

[0044] CALB, purchased from Novozymes (China) Investment Co., Ltd., specification >5000LU / g;

[0045] CTAB, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., specification 99%;

[0046] Dimethyl carbonate (DMC) was purchased from Tianjin Damao Chemical Reagent Factory, analytical grade;

[0047] Glycerol (GL) was purchased from Tianjin Dengfeng Chemicals Co., Ltd., analytical grade;

[0048] TEOS was purchased from Tianjin Dengfeng Chemicals Co., Ltd., analytical grade;

[0049] APTES was purchased from Tianjin Dengfeng Chemicals Co., Ltd. of analytical grade.

[0050] Example 1

[0051] S1. Add 1.0g hexadecyltrimethylammonium bromide (CTAB), 1.0g n-butanol, 30g urea aqueous solution (0.4M) and 12g cyclohexane to a 100mL round-bottom flask and mix, ultrasonically disperse for 30min to make the emulsion uniform, then stir slightly to observe whether it is uniform. The above operation can be carried out at room temperature. Then add 2.0g tetraethyl orthosilicate (TEOS) dropwise, stir for 30min, after the tetraethyl orthosilicate is uniformly dispersed, heat to 70-80°C, keep warm for 20-24h, then centrifuge the solid and liquid, wash the solid product with ethanol, dry and calcine in a resistance furnace, the calcination temperature is 550-600°C, the time is 5-5.5h, and a white powder, i.e., nano silicon oxide (DFSP), is obtained.

[0052] S2, taking 1.0g of nano silicon oxide (DFSP), 0.5mL of dichlorodimethylsilane and 100mL of toluene and mixing them, after the reaction is completed at room temperature, washing the solid matter with toluene and ethanol to obtain dichlorodimethylsilane-modified nano silicon oxide;

[0053] S3, take 5 mL of lipase solution, 15 mg of dichlorodimethylsilane-modified nano-silica and 50 mM phosphate buffer solution (PBS), put them into a 10 mL centrifuge tube, place them in a shaker at room temperature, and then centrifuge the solid and liquid for 2.5-3 hours, wash the solid with phosphate buffer solution, and freeze-dry to obtain immobilized enzyme I (CALB@DFSP). The lipase in this example is Candida antarctica lipase B (CALB). The SEM (scanning electron microscope) image of CALB@DFSP is as follows Figure 2 (a) shows the TEM (transmission electron microscope) image of CALB@DFSP. Figure 3 (a) shown.

[0054] S4. Take 50 mg of immobilized enzyme I, 9 mL of tris-HCl buffer solution (Tris-HCl), and 86 μL of tetraethyl orthosilicate, mix them, incubate them in a shaker at 25°C for 1-1.5 hours, and then add 21 μL of 3-aminopropyltriethoxysilane (APTES). The reaction time can be determined according to the required coating thickness, such as 2-12 hours. After the reaction, the solid and liquid are separated by centrifugation. The solid is washed with tris-HCl buffer solution, and aged in the above buffer solution at 25°C for 12 hours to obtain the immobilized enzyme (CALB@DFSP-OS). The SEM images of the above 3-aminopropyltriethoxysilane condensation reaction on the surface of immobilized enzyme I with a continuous reaction time of 4 hours, 8 hours, and 12 hours are shown in the figure below. Figure 2 (bd) As shown in Figure 2, TEM images of the condensation reaction of 3-aminopropyltriethoxysilane on the surface of immobilized enzyme I with a reaction time of 2h, 4h, 6h, 8h, 10h and 12h are shown in Figure 2. Figure 3 (bg) The HRTEM images of CALB@DFSP-OS obtained under 8h conditions are shown in Figure 3 As shown in (h), the thickness of the organic silicon layer is about 15 nm.

[0055] Depend on Figure 2 It can be seen that the surface of CALB@DFSP has obvious dendritic fiber-shaped open pore structure before reaction. As time goes by, a shell structure gradually forms on the surface of the particles, and the pores gradually become blurred. After 12 hours, the surface gradually agglomerates to form granular attachments. In addition, the particles obtained at different coating times are well dispersed, and the particle size does not change much compared with the CALB@DFSP without silicon shell coating. Figure 3 It can be clearly seen that as time goes by, the shell layer gradually becomes more obvious. After 2 hours of coating, the growth of the shell layer has no obvious effect on the internal structure of CALB@DFSP. When the time is extended to 8 hours, a clear shell structure has been formed. After 10 hours and 12 hours, the coating completely covers the immobilized enzyme. Combining the above SEM and TEM characterizations, it can be seen that the controllable preparation of the surface shell layer is achieved by regulating the coating time. In addition, it can be proved that the organic shell growth process maintains the original morphology of CALB@DFSP.

[0056] The CALB@DFSP-OS obtained at different coating times were characterized by N2 adsorption-desorption method.

[0057] like Figure 4 The curves shown in the figure are the N2 adsorption-desorption curves of CALB@DFSP-OS obtained after coating for different times (4h, 8h and 12h). It can be seen that the samples obtained at different coating times all have typical type IV isotherms and H1 type hysteresis loops, indicating that the particle surface still has a rich mesoporous structure after silicone coating. In addition, the specific surface areas of CALB@DFSP-OS-4h, CALB@DFSP-OS-8h and CALB@DFSP-OS-12h are 333.54m 2 / g, 241.23m 2 / g and 73.29m2 / g, which are significantly lower than the aforementioned CALB@DFSP (410.9m2 / g). This phenomenon is attributed to the entry of ethyl orthosilicate into the pores during the mixing process with CALB@DFSP. The organic silicon formed during the later induction of silane polycondensation occupies a certain space, resulting in a decrease in specific surface area and pore volume. In addition, as the coating time increases, the internal pore structure is gradually occupied. This characterization also shows the successful coating of the organic silicon shell layer.

[0058] CALB@DFSP and CALB@DFSP-OS were characterized by FTIR to analyze the functional group changes of the samples before and after CALB immobilization. Figure 5 As shown, the two samples have 1092 cm -1 The characteristic peak at 3428 cm is attributed to the vibration absorption of Si-O. -1 The characteristic peak at 1550cm is attributed to Si-OH. -1 The characteristic peaks are attributed to the stretching vibration of the amide bond (-CO-NH-). As can be seen from the figure, there is no obvious difference between the curves of CALB@DFSP and CALB@DFSP-OS samples. Since the immobilization of CALB was completed and some groups were introduced into the immobilized enzyme before the silicone coating, the similar characteristic peaks can indicate that the silicone coating process did not have a significant impact on the surface groups of the immobilized enzyme.

[0059] CALB@DFSP-OS was prepared by forming an organosilicon shell by silane polycondensation on the surface of the immobilized enzyme CALB@DFSP, so as to achieve good protection of the enzyme molecular conformation in the pores and improve the stability of the immobilized enzyme. The above SEM and TEM characterization results can prove that the controllable preparation of the shell layer is achieved by controlling the coating time. In addition to directly affecting the structural characteristics of CALB@DFSP-OS such as specific surface area and pore volume, the construction of the shell layer will also directly affect the enzyme activity of CALB@DFSP-OS. Taking the activity of CALB@DFSP as a control, Figure 6 The figure shows the effect of different coating time on the enzyme activity of CALB@DFSP-OS. It can be seen from the figure that the relative activity of the immobilized enzyme shows a downward trend with the extension of the shell coating time. Compared with the uncoated CALB@DFSP enzyme activity, when the coating time is 2h, there is no obvious shell, and the immobilized enzyme activity only shows a slight decrease, with a relative enzyme activity of 96.15%. After 4h of coating, the shell is initially formed, about 3nm, and the remaining relative enzyme activity is 92.33%. When the coating time is 6h (shell is about 10nm) and 8h (shell is about 15nm), a complete shell is gradually formed, and the relative enzyme activity decreases to 86.28% and 76.93%, respectively. When the coating time is 10h and 12h, the shell thickness is about 20nm, and the effect on the enzyme activity becomes more and more obvious, and the relative enzyme activity decreases to 60.41% and 48.06%, respectively. The above phenomenon occurs mainly because the thickness of the silicone layer increases with the extension of coating time, the carrier shielding effect becomes more obvious, hindering the contact between the enzyme molecules and the substrate, and increasing the mass transfer resistance, causing the apparent activity to decrease.

[0060] In order to further explore the effect of organic shell thickness on the stability of CALB@DFSP-OS and determine the optimal coating time, Figure 7The figure shows the change of relative activity of immobilized enzyme over time at 300rpm. With the extension of shaking time, the relative activity of CALB@DFSP-OS-2h and CALB@DFSP-OS-4h decreased significantly, showing the same change trend as uncoated CALB@DFSP; after shaking for 10h, the activity of CALB@DFSP-OS-2h and CALB@DFSP-OS-4h had decreased by about 30%, and after 25h, it decreased by more than 50%. This phenomenon is due to the fact that the organic silicon layer was not fully formed due to the short coating time, and only part of the immobilized enzyme was covered, while most of the enzyme molecules were still directly exposed to the reaction medium during the shaking process, and the violent shaking would also cause the leakage of enzyme molecules. It can be seen from the change curve of CALB@DFSP-OS-6h that its relative activity showed a slow downward trend with the extension of shaking time, which was mainly due to the protective effect of the gradual formation of the shell on the enzyme molecules. After shaking for 25h, 68.97% of the initial activity remained. In comparison, CALB@DFSP-OS-(8h, 10h, 12h) with a complete shell has significantly improved stability under oscillation conditions. After 10h and 25h of oscillation reaction, CALB@DFSP had 59.98% and 41.09% remaining activity, while CALB@DFSP-OS-8h maintained 95.13% and 89.67% relative activity, respectively. This shows that the organic shell effectively prevents enzyme denaturation and loss through the binding effect. Based on the previous analysis, CALB@DFSP-OS-8h prepared under the coating time of 8h has high initial activity and good stability. Considering the later application needs, it will be used for further research.

[0061] Comparative Example 1

[0062] This comparative example uses lipase (CALB) that is not immobilized on a nano-silica carrier.

[0063] The above embodiments and comparative examples were subjected to performance tests, and the test contents are as follows.

[0064] pH stability of CALB@DFSP-OS

[0065] CALB@DFSP-OS and free enzyme CALB were incubated in pH 4.0 and pH 11.0 buffer solutions, respectively, and taken out at intervals of 12 h to measure the changes in their hydrolytic activity and calculate the relative activity. The activity of CALB@DFSP-OS and free enzyme CALB changed with time at pH = 4.0 as shown in Figure 2. Figure 8 As shown in (a), at pH = 11.0 Figure 8 (b) as shown.

[0066] Under both pH conditions, the free enzyme CALB showed a more obvious downward trend, and after 96 h, the free enzyme retained 24.38% and 38.42% relative activity at pH 4.0 and pH 11.0, respectively. In comparison, CALB@DFSP-OS retained 75.09% and 85.74% relative enzyme activity at pH 4.0 and pH 11.0, respectively.

[0067] This indicates that changes in solution pH will seriously affect the dissociation state of the amino acid side chain groups on the active site of the enzyme molecule, which in turn directly affects the affinity between the enzyme and the substrate and the activation of the enzyme. Long-term acidic or alkaline conditions will have a serious impact on the activity of the enzyme. Generally speaking, CALB is more stable under alkaline conditions than under acidic conditions. The stability of CALB@DFSP-OS is due to the protective effect of the external shell and internal pore structure on the conformation of the enzyme molecule. The silicone coating on CALB@DFSP-OS can effectively avoid the influence of extreme pH on the amino acid side chains, further improving the stability of the immobilized enzyme.

[0068] Thermal stability of CALB@DFSP-OS

[0069] Appropriate amounts of free CALB and CALB@DFSP-OS were immersed in cyclohexane at 60°C for a period of time (12h, 24h, 36h, 48h, and 60h). After cooling, the changes in their hydrolysis activities were measured, and the relative activities were calculated.

[0070] Fig. 9 The thermal stability of CALB@DFSP-OS and free CALB at 60°C is shown. Fig. 9 As shown in the figure, after 60 hours, CALB@DFSP-OS can retain 90.35% of the initial enzyme activity, while the remaining activity of free CALB is only 50.12%, indicating that the inactivation of CALB@DFSP-OS is significantly lower than that of free CALB under high temperature incubation conditions. This phenomenon is mainly attributed to: (1) the organosilicon coating further encloses the enzyme molecules adsorbed in the carrier pores in the shell structure, which is more conducive to the enzyme molecules to maintain a complete active conformation; (2) the organosilicon coating has a good thermal barrier effect, so that the enzyme molecules will not be directly exposed to the external thermal environment; (3) by effectively binding the enzyme molecules, the leakage of enzyme molecules during long-term reactions is reduced.

[0071] Storage stability of CALB@DFSP-OS

[0072] A certain amount of free CALB and CALB@DFSP-OS were stored at 4°C for 60 days. Appropriate amounts of free CALB and CALB@DFSP were taken out at regular intervals to measure the changes in their hydrolysis activities and calculate their relative activities.

[0073] like Fig.10 The figure shows the storage stability of CALB@DFSP-OS. Fig.10 It can be seen that CALB@DFSP-OS maintained a high relative activity throughout the storage period, with the relative enzyme activities of 94.49% and 91.82% at 30d and 60d, respectively. In comparison, the relative activity of the free enzyme decreased significantly at the same storage time, which was 59.63% and 45.65%, respectively. This is because the surface organic silicon layer coated by CALB@DFSP-OS produces a confinement effect that limits the conformational changes of the CALB molecules, inhibits the distortion or structural changes of the active sites and spatial conformations caused by adverse factors, and enhances the rigidity of the enzyme molecules. In addition, this organic coating can also effectively avoid the loss of enzyme activity caused by the leakage of enzyme molecules during long-term storage, thereby improving the stability of CALB@DFSP-OS. The decrease in the activity of CALB@DFSP-OS in the later stage of the experiment may be due to the natural deformation of the secondary structure of the enzyme protein, including but not limited to the reduction of α-helix and β-fold.

[0074] The present application further proposes an application of the above-mentioned immobilized enzyme, when the enzyme solution is a lipase solution, the immobilized enzyme is used to catalyze transesterification reaction. Lipase is a class of enzymes with multiple catalytic abilities, which can catalyze the hydrolysis, alcoholysis, esterification, transesterification and reverse synthesis of some water-insoluble esters. When the immobilized enzyme prepared by the above method is used for catalysis, the immobilized enzyme can have good stability while maintaining a high enzyme activity, thereby improving the efficiency of the transesterification reaction.

[0075] The above-mentioned immobilized enzyme can be used in a method for preparing glycerol carbonate, wherein the above-mentioned immobilized enzyme is used to catalyze the transesterification reaction between glycerol (GL) and dimethyl carbonate to obtain glycerol carbonate (GC). The reaction equation is as follows:

[0076]

[0077] Application Examples

[0078] The CALB@DFSP-OS of Example 1 was used to repeatedly catalyze the synthesis of GC, and the reaction results were analyzed by gas chromatograph, and the GL conversion rate and GC yield were calculated. The calculation method of the GL conversion rate and GC yield is as follows:

[0079]

[0080]

[0081] After each batch of reaction, the immobilized enzyme was recovered, washed three times and put into the next batch. CALB@DFSP and lipase N435 with the same enzyme activity were used to catalyze the synthesis of GC under the same conditions, and the reaction results were analyzed to evaluate its repeated use stability.

[0082] In the transesterification reaction of GC, the GC yield was used as an evaluation index to compare the reusability of CALB@DFSP-OS, CALB@DFSP and lipase N435 as catalysts. Fig.11 As shown. Under 55 ° C, tert-butyl alcohol was used as the solvent, the amount of each catalyst was 16.00% of the mass ratio of GL, and the molar ratio of GL to DMC was 1:10. The GC yields of CALB@DFSP-OS, CALB@DFSP and N435 obtained in the first use were 84.65%, 88.26% and 92.31%, respectively. After CALB@DFSP-OS was reused 10 times, the GC yield decreased to 77.02%, which was equivalent to retaining 90.98% of the initial enzyme activity. In the same operation process, the GC yield of CALB@DFSP after 10 reuses was 68.75%, and the relative initial activity remained 77.89%. However, after the commercial N435 was used 10 times, the GC yield was only 32.88%, and the relative initial activity remained 35.62%. It can be seen that CALB@DFSP-OS has good repeated use stability and there is no obvious decline in multiple batches of repeated use.

[0083] The catalytic activity of CALB@DFSP-OS is close to that of CALB@DFSP, and its repeated stability is better than that of CALB@DFSP. The main reasons are as follows: (1) The coating effectively improves the rigidity of the immobilized enzyme, preventing the leakage of CALB during the reaction and the physical breakage of the immobilized enzyme by long-term reaction; (2) The hydrophobic groups of the silicone coating provide a relatively hydrophobic microenvironment for CALB, which plays a role in interfacial activation; (3) The external coating effectively prevents GL from being directly exposed in the open structure and being damaged by methanol in the active center; (4) CALB@DFSP-OS with a hydrophobic surface has good dispersibility in non-aqueous phase reactions, which is conducive to the diffusion of substrates and contact with CALB. Compared with the macroporous resin carrier used for immobilized lipase N435, the dendritic fiber-shaped channels and silicone coating of CALB@DFSP-OS can provide better rigid support and conformational protection for CALB, as well as better mechanical stability, thus showing better stability than N435 in multiple batch reactions. The reason for the decrease in GC yield after repeated use of CALB@DFSP-OS may be that the byproducts methanol and GL are adsorbed and accumulated on the surface and inside of the immobilized enzyme, causing the enzyme to gradually inactivate. In addition, the partial loss of the immobilized enzyme during the washing operation is also an important reason for the decrease in GC yield.

[0084] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0085] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for preparing an immobilized enzyme, characterized in that: The preparation method comprises the following steps: S1. Hexadecyltrimethylammonium halide, n-butanol, urea aqueous solution and cyclohexane are mixed, dispersed uniformly by ultrasonication, ethyl orthosilicate is added dropwise, stirred uniformly, heated to 70-80°C, kept warm, and then centrifuged to separate the solid and liquid, wash the solid product, dry it and calcine it to obtain nano silicon oxide; S2, mixing the nano-silicon oxide, dichlorodimethylsilane and toluene, and washing after the reaction to obtain dichlorodimethylsilane-modified nano-silicon oxide; S3, taking the enzyme solution, the dichlorodimethylsilane-modified nano-silica and the phosphate buffer solution and placing them in a shaker for shaking, then centrifuging the solid and the liquid for separation, washing the solid with a phosphate buffer solution, and freeze-drying to obtain the immobilized enzyme I; S4, taking the immobilized enzyme I, tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and tetraethyl orthosilicate, mixing them, incubating them in a shaker, and then adding 3-aminopropyltriethoxysilane. After the reaction, the solid and liquid are separated by centrifugation; taking the solid, washing it with tris(hydroxymethyl)aminomethane hydrochloride buffer solution, standing it for aging, and obtaining the immobilized enzyme; the incubation time of the immobilized enzyme I and the 3-aminopropyltriethoxysilane in step S4 is 5:(1-1.5).

2. The method for preparing an immobilized enzyme according to claim 1, characterized in that: The mass ratio of the dichlorodimethylsilane-modified nano-silicon oxide to the enzyme in step S3 is 3:(1.5-5).

3. The method for preparing an immobilized enzyme according to claim 1, characterized in that: The mass volume ratio of the immobilized enzyme I to the tetraethyl orthosilicate in step S4 is 1:(2-2.5).

4. The method for preparing an immobilized enzyme according to claim 1, characterized in that: The incubation time in step S4 is 0.5-2h, the incubation temperature is 20-30°C, and the rotation speed of the shaking table is 50-200rpm.

5. The method for preparing an immobilized enzyme according to any one of claims 1 to 4, characterized in that: The enzyme solution includes lipase, one of oxidoreductases, transferases, hydrolases, lyases, isomerases, and synthetases.

6. An immobilized enzyme, characterized in that: The immobilized enzyme is prepared by the method for preparing the immobilized enzyme according to claims 1-5.

7. A use of the immobilized enzyme according to claim 6, characterized in that: When the enzyme solution is a lipase solution, the immobilized enzyme is used to catalyze one of a hydrolysis reaction, an esterification reaction, and an ester exchange reaction.

8. A method for preparing glycerol carbonate, characterized in that: When the enzyme solution is a lipase solution, the preparation method is to use the immobilized enzyme described in claim 6 to catalyze the transesterification reaction between glycerol and dimethyl carbonate to obtain glycerol carbonate.

Citation Information

Patent Citations

  • A method of utilizing Pickering emulsion immobilized enzyme for a fixed-bed continuous reaction

    CN107287181A

  • Flower-shaped silicon oxide nanoparticle vaccine and preparation method thereof

    CN111388663A

  • Preparation method and application of organic silicon cell coating

    CN113355261A